2011
DOI: 10.1007/s12237-011-9390-x
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Mediterranean Deltaic and Lagoon Wetlands with Sea-Level Rise: The Importance of River Input

Abstract: We report on a decadal trend of accretionary dynamics in the wetlands of several northwestern Mediterranean deltas and a lagoon system, all of them with high rates of wetland loss. Wetland vertical accretion and surface elevation change were measured at 55 riverine, marine, and impounded sites in four coastal systems: the Ebro delta, Spain; the Rhône delta, France; and the Po delta and Venice Lagoon, Italy. Vertical accretion and elevation change ranged between 0 and 25 mm year −1 and were strongly correlated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 58 publications
5
31
0
1
Order By: Relevance
“…Since many of the wetlands most susceptible to sea-level rise are deficient of mineral sediment (e.g. Kirwan et al, 2010;Day et al, 2011), we suggest that once the primary productivity of a marsh starts to decline, sustained and perhaps accelerated rates of decomposition will only exacerbate the syndrome through loss of elevation.…”
Section: Discussionmentioning
confidence: 95%
“…Since many of the wetlands most susceptible to sea-level rise are deficient of mineral sediment (e.g. Kirwan et al, 2010;Day et al, 2011), we suggest that once the primary productivity of a marsh starts to decline, sustained and perhaps accelerated rates of decomposition will only exacerbate the syndrome through loss of elevation.…”
Section: Discussionmentioning
confidence: 95%
“…Crucially, however, previous studies have revealed high acrosssite variability in the processes that contribute to surface elevation change [32][33][34] , making assumptions of uniformity in processes across wetlands inappropriate. This highlights the need for site-specific data that accurately represent local processes to initialize, calibrate and validate site-specific wetland models, and to evaluate the outcome of different SLR scenarios 35,36 .…”
Section: Critical Gaps In Quantifying Coastal Wetland Vulnerabilitymentioning
confidence: 99%
“…These processes of floodplain and delta inundation and draining have built land along river corridors and in deltas around the world [38,46,[48][49][50][51]. Where levees have not stopped river floods, overbank flooding still occurs, such as in the Danube [52], northwestern Mediterranean deltas [53] and for the Atchafalaya delta of the Mississippi [48], and leads to more sustainable wetlands. There is a general consensus that major world deltas will become smaller in the 21st century due to accelerated sea-level rise and a reduction in sediment input (e.g., [54]).…”
Section: Discussionmentioning
confidence: 99%